Bubble cloud dynamics in an ultrasound field. (16th January 2019) - Maeda, Kazuki; Colonius, Tim
Abstract : The dynamics of bubble clouds induced by high-intensity focused ultrasound is investigated in a regime where the cloud size is similar to the ultrasound wavelength. High-speed images show that the cloud is asymmetric; the bubbles nearest the source grow to a larger radius than the distal ones. Similar structures of bubble clouds are observed in numerical simulations that mimic the laboratory experiment. To elucidate the structure, a parametric study is conducted for plane ultrasound waves with various amplitudes and diffuse clouds with different initial void fractions. Based on an analysis of the kinetic energy of liquid induced by bubble oscillations, a new scaling parameter is introduced to characterize the dynamics. The new parameter generalizes the cloud interaction parameter originally introduced by d'Agostino & Brennen ( J. Fluid Mech., vol. 199, 1989, pp. 155–176). The dynamic interaction parameter controls the energy localization and consequent anisotropy of the cloud. Moreover, the amplitude of the far-field, bubble-scattered acoustics is likewise correlated with the proposed parameter. Findings of the present study not only shed light on the physics of cloud cavitation, but may also be of use for the quantification of the effects of cavitation on outcomes of ultrasound therapies including high-intensity focused ultrasound-based lithotripsy.